JAK2V617F but not CALR mutations confer increased molecular responses to interferon-α via JAK1/STAT1 activation - Czech, Julia; Cordua, Sabrina; Weinbergerova, Barbora; Baumeister, Julian; Crepcia, Assja; Han, Lijuan; Maié, Tiago; Costa, Ivan G; Denecke, Bernd; Maurer, Angela; Schubert, Claudia; Feldberg, Kristina; et al. (Leukemia, 2019)
Pegylated interferon-α (peg-IFNa) treatment induces molecular responses (MR) in patients with myeloproliferative neoplasms (MPNs), including partial MR (PMR) in 30-40% of patients. Here, we compared the efficacy of IFNa treatment in JAK2V617F- vs. calreticulin (CALR)-mutated cells and investigated the mechanisms of differential response. Retrospective analysis of MPN patients treated with peg-IFNa demonstrated that patients harboring the JAK2V617F mutation were more likely to achieve PMR than those with mutated CALR (p = 0.004), while there was no significant difference in hematological response. In vitro experiments confirmed an upregulation of IFN-stimulated genes in JAK2V617F-positive 32D cells as well as patient samples (peripheral blood mononuclear cells and CD34+ hematopoietic stem cells) compared to their CALR-mutated counterparts, and higher IFNa doses were needed to achieve the same IFNa response in CALR- as in JAK2V617F-mutant 32D cells. Additionally, Janus-activated kinase-1 (JAK1) and signal transducers and activators of transcription 1 (STAT1) showed constitutive phosphorylation in JAK2V617F-mutated but not CALR-mutated cells, indicating priming towards an IFNa response. Moreover, IFN-induced growth arrest was counteracted by selective JAK1 inhibition but enhanced by JAK2 inhibition. In conclusion, our data suggest that, clinically, higher doses of IFNa are needed in CALR-mutated vs. JAK2V617F-positive patients and we suggest a model of JAK2V617F-JAK1/STAT1 crosstalk leading to a priming of JAK2V617F-positive cells to IFNa resulting in differential sensitivity.
Keywords: Prognosis; Janus Kinase 2; myši; nádorové buňky kultivované; Cell Proliferation; Adult; senioři; Aged; Male; apoptóza; Retrospective Studies; lidé; lidé středního věku; Humans; Mutation; Janus Kinase 1; retrospektivní studie; Myeloproliferative Disorders; Middle Aged; Biomarkers, Tumor; nádorové biomarkery; Mice; Animals; proliferace buněk; interferon alfa; Interferon-alpha; Apoptosis; zvířata; transkripční faktor STAT1; antivirové látky; Antiviral Agents; mužské pohlaví; Janus kinasa 1; následné studie; dospělí; STAT1 Transcription Factor; Janus kinasa 2; kalretikulin; ženské pohlaví; Tumor Cells, Cultured; mutace; myeloproliferativní poruchy; Female; Follow-Up Studies; prognóza; Calreticulin